2011
DOI: 10.1007/s11432-010-4155-x
|View full text |Cite
|
Sign up to set email alerts
|

The structural analysis of fuzzy measures

Abstract: From quotient space based granular computing theory we explore the fuzzy measures of fuzzy sets. Based on the structural analysis of fuzzy sets, we present an "isotropism" assumption. Under this assumption we achieved the following insights: (1) the uniqueness of a fuzzy measure being isotropic on a finite complete semi-ordered set; (2) the necessary and sufficient condition of the isomorphism for fuzzy measure functions in fuzzy mathematics; (3) the necessary and sufficient condition that fuzzy measures have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thanks to the flexibility of the model, NMF is particularly suitable for the detection of overlapping communities [8,[23][24][25]. The result U can be interpreted as a cluster membership degree matrix, i.e., node i belongs to a community t with the strength U it (note that j U ij = 1), providing "fuzzy" overlapping communites.…”
Section: A Motivationmentioning
confidence: 99%
“…Thanks to the flexibility of the model, NMF is particularly suitable for the detection of overlapping communities [8,[23][24][25]. The result U can be interpreted as a cluster membership degree matrix, i.e., node i belongs to a community t with the strength U it (note that j U ij = 1), providing "fuzzy" overlapping communites.…”
Section: A Motivationmentioning
confidence: 99%
“…It is well known that the chaotic system has the characteristics of sensitivity of initial value and complexity of trajectory, so chaos has great potential application in many engineering fields, such as weak signal detection, [1][2][3][4] random number generator, [5,6] secure communication, [7][8][9][10][11][12][13] and image encryption. [14][15][16][17][18][19][20] Furthermore, Lin et al [21,22] studied the influence of electromagnetic radiation on the chaotic characteristics of neural networks, and found that appropriate electromagnetic radiation is helpful to treat some neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Just as a big umbrella it covers all the research on the theories, methodologies, technologies, and tools about granules, especially, under the concept of GrC, L. Zhang and B. Zhang [18][19][20][21][22][23][24] focus on the equivalence relationship among different grain-size worlds and on the problem that is mainly based on fuzzy sets, i.e., quotient space theory, fuzzy quotient space. In quotient space theory, hierarchical structures are expressed by the relationship on crisp sets in [20,24], and it is a core concept. The matrix is objective, operative, and can describe binary relations on crisp sets.…”
Section: Introductionmentioning
confidence: 99%